Atmosphere teleconnections from abatement of China aerosol emissions exacerbate Northeast Pacific warm blob events - Wang, Hai (author); Zheng, Xiao-Tong (author); Cai, Wenju (author); Han, Zi-Wen (author); Xie, Shang-Ping (author); Kang, Sarah M. (author); Geng, Yu-Fan (author); Liu, Fukai (author); Wang, Chuan-Yang (author); Wu, Yue (author); Xiang, Baoqiang (author); Zhou, Lei (author) (Proceedings of the National Academy of Sciences, 2024)
During 2010 to 2020, Northeast Pacific (NEP) sea surface temperature (SST) experienced the warmest decade ever recorded, manifested in several extreme marine heatwaves, referred to as "warm blob" events, which severely affect marine ecosystems and extreme weather along the west coast of North America. While year - toyear internal climate variability has been suggested as a cause of individual events, the causes of the continuous dramatic NEP SST warming remain elusive. Here, we show that other than the greenhouse gas (GHG) forcing, rapid aerosol abatement in China over the period likely plays an important role. Anomalous tropospheric warming induced by declining aerosols in China generated atmospheric teleconnections from East Asia to the NEP, featuring an intensified and southward - shifted Aleutian Low. The associated atmospheric circulation anomaly weakens the climatological westerlies in the NEP and warms the SST there by suppressing the evaporative cooling. The aerosol - induced mean warming of the NEP SST, along with internal climate variability and the GHG - induced warming, made the warm blob events more frequent and intense during 2010 to 2020. As anthropogenic aerosol emissions continue to decrease, there is likely to be an increase in NEP warm blob events, disproportionately large beyond the direct radiative effects.